Analisis Determinan Rating Sukuk Korporasi Di Indonesia - Faruq, Umarul (Shafin: Sharia Finance and Accounting Journal, 2021)
This research is aimed to collect empirical evidences and knowing the significance of the influence of maturity, firm size, growth, profitability, liquidity, and leverage on corporate sukuk ratings in Indonesia, and testing theories about the determinants of sukuk ratings. The population of this research is all corporate sukuk in Indonesia which have been rated by Pefindo. The sampling technique in this study uses a purposive sampling method so that the research sample was 124 sukuk issued by 26 companies and rated by Pefindo in the 2014-2018 period. The method of data collection uses the library research approach. The data analysis technique uses Structural Equetion Modeling with Partial Least Square using SmartPLS 3.0 software. The results of this study indicate that the variables of firm size, growth, and liquidity each have a significant positive effect on the sukuk rating, while the leverage variable has a significant negative effect on the sukuk rating. The profitability and maturity variables have no significant effect on sukuk rating.